Etyczne wyzwania w przemyśle farmaceutycznym. Zarys problematyki - Kaczmarek, Emilia (Annales. Etyka w Życiu Gospodarczym, 2015)
The goal of the text is to show which actions of the modern pharmaceutical industryare morally controversial. There are several burning issues that we need to face onthis field, such as: How to deal with the conflict of interests within the medicine?How to mark the vanishing boundaries between information and advertisement concerningthe pharmaceutical education? How does the drug advertisement lead to thepharmaceuticalization of society? In the text all of these problems will be brieflyanalysed. The article has an introductory character, it may serve as an overview ofthe burning issues in the pharmaceutical industry ethics – all questions that areposed in the text need further examination.